Ethical Behavior Of Islamic Bank Services In Indonesia : A Bibliometric Study - Ainorrofiqie Ainorrofiqie (Journal of Islamic Economics and Finance, 2023)
Ethics relates to good living habits, both in a person and in a society or community group. This means that ethics are related to values, good ways of life, good rules of life, and all habits that are adopted and passed from one person to another or from one generation to another. Islamic Bank Services In Indonesia (BPRS) formulates ethical Islamic work ethics which in the form of its main values is an elaboration of ethical values applied by all BPRS employees (employees). This study conducted a qualitative mapping of research articles on ethical behavior in service from 2019 to 2023, focusing on the year of publication, theories used and research variables. A total of 100 articles from accredited journals on Google Scholar were included in the analysis. In this study assisted by two software including publish or perish software and VOSviewer. The theory of ethical behavior in Islamic banking services is found to be a theory that is considered to be used quite often, but the relationship between the ethical behavior of servants in Islamic banks and fukus is that BPRS is still very rare. Software publish or perish and VOSviewer. Publish or perish software for data collection while VOSviewer software to get 3 outputs that will be analyzed with a bibliometric approach including Network Visualization, Overlay Visualization and Density Visualization. From the results of the analysis of the three outputs, it can be concluded that the theory or topic of ethical behavior and Islamic banking was found to be a theory that has been used since 2019 and is quite often used, but the relationship of the theory of Islamic bangking ethical behavior is not found related, or you could say the theory of Islamic bangking ethical behavior theory has never been made as a research topic in the span of 2019 until 2023.